2017
DOI: 10.5796/electrochemistry.85.384
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Immunosensor for Aflatoxin B<sub>1</sub> Based on Polyaniline/Graphene Nanohybrids Decorated with Au Nanoparticle

Abstract: A novel method for preparing polyaniline/graphene (PANI/GN) nanocomposites was demonstrated by liquid-liquid interface polymerization method. Then the gold nanoparticles (Au NPs) were uniformly decorated on the PANI/GN surface to form gold/polyaniline/graphene (Au/PANI/GN) nanohybrids. The Au/PANI/GN nanohybrids film showed good electron transfer ability, which ensured high sensitivity to detect AFB 1 in a range from 0.05 to 25 ng/mL with a detection limit of 0.034 ng/mL obtained at 3σ (n = 10). The proposed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The ∆E p value increased to 198 mV, and the I pa and I pc values decreased to 144.7 µA and −163.4 µA, respectively. The results indicated that the immunoreaction occurred, and the AFB 1 captured on the electrode surface hindered the reaction of [Fe(CN) 6 ] 3− , indicating the successful formation of the immune complex on the electrode surface [29].…”
Section: Characterization Of the Immunosensormentioning
confidence: 99%
“…The ∆E p value increased to 198 mV, and the I pa and I pc values decreased to 144.7 µA and −163.4 µA, respectively. The results indicated that the immunoreaction occurred, and the AFB 1 captured on the electrode surface hindered the reaction of [Fe(CN) 6 ] 3− , indicating the successful formation of the immune complex on the electrode surface [29].…”
Section: Characterization Of the Immunosensormentioning
confidence: 99%
“…With the development of the application of graphene nanomaterials in aflatoxin analysis and detection, researchers have also tried to combine precious metals, ionic liquids or conductive polymers with graphene nanomaterials to improve the performance of aflatoxin electrochemical analysis. Shi [58] introduced nanogold-modified PANI/graphene nanocomposites and fixed them on a gold electrode to form an Au/PA-NI/G/Au electrode detection sensor. The electrochemical analysis method for AFB1 was established by immune reaction and square wave cyclic voltammetry (SWV).…”
Section: Graphene Nanomaterialsmentioning
confidence: 99%